X-ray Photoelectron Spectroscopy (XPS) Analysis of Undoped ZnO and ZnO:Er Thin Films - Iwan Sugihartono; Esmar Budi; Agus Setyo Budi (Jurnal ILMU DASAR, 2015)
Undoped ZnO and ZnO:Er  thin films were deposited on p-type Si substrates by ultrasonic spray pyrolisis (USP). Undoped and ZnO:Er thin films have been analyzed by using X-ray Photoelectron Spectroscopy (XPS). The results show that the XPS spectrum has two Er peak at ∼157 eV and ∼168 eV. The XPS Zn 2p spectrum of undoped ZnO and ZnO:Er thin films have binding energy for Zn 2p3/2 (~ 1021 eV) and Zn 2p1/2 (~1045eV) were found no shift in binding energy after the incorporation of Er. Meanwhile, after Er incorporates into ZnO, the O 1s spectrum is composed two peak of binding energy (BE) at ~530.5eV and the shoulder about 532.5 eV.Keywords: ZnO thin films, ZnO:Er, XPS, binding energy